Evaluation of Soil Fertility for Horticultural Planting in Post-Eruption of Mount Sinabung Land Recovery - Sihaloho, Nani Kitti; Sinaga, Roida; Gracia, Sarah (Universitas Quality, 2023)
Evaluation of Soil Fertility for Horticultural Plantings in Land Recovery After the Eruption of Mount Sinabung. Karo Regency. North Sumatra is known as a center for Horticultural production (vegetables, fruits and ornamental plants) where the livelihoods of the population are primarily food crop and horticulture farming as well as mixed plantations. Karo Regency also has a volcano that is active again in Indonesia, namely Mount Sinabung. Mount Sinabung after approximately 10 years after the eruption, namely the eruption on August 27 2010, after the eruption of Mount Sinabung that volcanic material deposits within a certain period of time will experience weathering. This weathering will produce fertile soil that can be used for horticultural crops. Minerals contained in volcanic eruptions will decay and release various nutrients that are fertile for plant needs. The purpose of this study was to determine the parameters of soil fertility in horticultural cropping land in Karo District after approximately 10 years of the eruption of Mount Sinabung in increasing horticultural crop production and influencing agriculture in the future. The research was carried out from April to December 2023 in Karo Regency. Soil analysis activities were carried out at the Research and Development Center Laboratory of PT. Nusa Pusaka Kencana Analytical & Oc. Laboratory of Baringan Tebing Tinggi Gardens, North Sumatra. Soil analysis tests in the laboratory were carried out to determine the soil fertility parameter values for horticultural plantings after the eruption of Mount Sinabung. Urgency This research determines the evaluation of soil fertility in horticultural crops, in Karo District after the Mount Sinabung Eruption for land recovery and food security in North Sumatra and can identify horticultural land that requires a special strategy in its management and land management in post-eruption land recovery of Mount Sinabung. The results showed that the status of soil fertility in Tigapanah District was that the land was not affected by the eruption of Mount Sinabung, namely Moderate, with the limiting factors for soil fertility being CEC with the Low and Medium categories, and soil Potassium content with very low criteria. The status of soil fertility in Nemanteran District with the condition of the land affected by the eruption of Mount Sinabung is Moderate with the limiting factor for soil fertility being KB in the Low category, and soil Potassium content with very low criteria.